Perancangan Sistem Informasi Penjualan Produk Frozen Food Menggunakan Metode Waterfall Berbasis Web dan Xammp - Iin Parlina; Mesinta Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This research was conducted to identify and analyze the problems occurring in UMKM regarding the processing of stock transactions, specifically in the business sector of frozen food products, which is still managed manually. This indicates that information technology optimization has not been thoroughly implemented by business actors in this field. Conventional recording processes frequently lead to errors in record-keeping, delays in report generation, and limitations in conveying product information to customers. Furthermore, the manual system poses challenges for business owners in monitoring stock in real-time, thereby hindering fast and accurate decision-making. Developing an information system for Frozen Food UMKM can help overcome these issues in processing frozen food product sales data, making it easier and more effective for system users to process or manage sales transactions. The research method used to build this information system is the Waterfall method, while data collection was carried out through direct observation by observing manual transaction processes directly and interview methods to obtain supporting information for this study. The result of this research is a system designed to provide convenience for UMKM the Frozen Food Product Sales Information System is implemented to process data effectively and efficiently. This system was designed using the PHP programming language with a MySQL database for database management, utilizing XAMPP for the MySQL database, and implemented using Visual Studio Code for the system interface. The research findings demonstrate that the developed system is capable of managing product data, sales transactions, and reports in a structured and integrated manner. The system also features data search functionalities, automated stock management, and faster, more accurate report generation. Consequently, the designed system can enhance operational efficiency and assist business operators in optimizing their business processes. Future research can achieve quality improvement and broader service coverage by developing a more complex system, integrating electronic payment functions, and system-based automatic notifications, alongside enhancing system security through routine software audits to achieve more efficient and beneficial performance.